When Michelangelo was modern : collecting, patronage and the art market in Italy, 1450-1650 - Reist, Inge Jackson; When Michelangelo was Modern: The Art Market and Collecting in Italy, 1450-1650 (Symposium) (2019 : Frick Collection) (Leiden ; Boston : Brill, 2022)
"Through case studies of collectors, patrons, and agents who redefined collecting and the art market, this volume illuminates how the changing status of the artist, rise of connoisseurship, role of intermediaries and new patterns of consumption established models for collecting and display that resemble those still practiced today. The book presents new research by recognized scholars who examine the motivations of collectors and agents, emphasizing how their collecting, patronage and advocacy could require support of artists whose reputations were not fully established. Together, the essays invite consideration of works that are familiar in art-historical terms but less so as markers of the socio-economic shifts of a particular cultural moment. This book evolved from a symposium "When Michelangelo was Modern: The Art Market and Collecting in Italy, 1450-1650," organized by the Center for the History of Collecting, that was held at The Frick Collection on April 12 and 13, 2019. Both the book and the symposium were made possible through the generous support of the Robert H. Smith Family Foundation. The book is published in association with The Frick Collection"--
Courtesans as Collectors and Tastemakers in Renaissance Italy / Chriscinda Henry -- Modern Michelangelos? Copies, Fakes, and New Economies of Taste in the Early Seicento / Hannah Joy Friedman -- Artists as Critics, and Critics as Artists: Collaboration and Inclination in Giulio Mancini's Taste Formation / Frances Gage.
"This book evolved from a symposium "When Michelangelo was Modern: The Art Market and Collecting in Italy, 1450-1650," organized by the Center for the History of Collecting, that was held at The Frick Collection on April 12 and 13, 2019"--Colophon.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 22, 2022).
eBooks on EBSCOhost
Keywords: Art patronage -- Italy; Art -- Collectors and collecting -- Italy; Art -- Marketing; Art and society -- Italy; Mécénat -- Italie; Art -- Collectionneurs et collections -- Italie; Art -- Commercialisation; Art et société -- Italie; art market; Art and society; Art -- Collectors and collecting; Art -- Marketing; Art patronage; Italy; Electronic book